Investigation on the Power Factor Correction Circuits for Switched Reluctance Motor Drives - Kumar, Manoj (My University, 2011)
Among the various electric drives available, switched reluctance motor (SRM) has become a popular choice for the domestic and industrial applications due to its simple and robust construction. Moreover, this motor does not have winding in the rotor; hence it is suitable for high speed applications (usually above 10000 rpm). These motor are extensively used in aerospace, automotive and other home appliances. The motor have winding in the stator which is excited from a separate source. The control of these motor drives is obtained using converter circuits that control the excitation of the phase by switching converter switches. The conventional converter circuit suffers from low power factor and high harmonic content which is turns affects the performance of the motor drive. The aim of the work is to develop a suitable converter circuit that could give an improved power factor and low current harmonic. Various converter topologies are studied and simulation of asymmetric bridge converter was carried out using MATLAB/SIMULINK to study its performance on the various parameters of the switched reluctance motor (SRM) drive. Further the simulations of Diode Bridge Rectifier circuit (DBR) and the Switching Power Converter with Power Factor Correction (SPC-PFC) are carried out. The performance of SPC-PFC is compared with the DBR circuit and it found that the SPC-PFC circuit proves to be a superior configuration for improving the power factor and mitigating the harmonic content in these drives.
M.E. (Power Systems and Electric Drives)
Keywords: Switched Reluctance Motor(SPM); Power Factor; SPC-PFC